Analysis of Dengue Virus Genotypes and Further Investigations for Mixed Infections Through RT-PCR in Classical Dengue Fever Patients in Pakistan - Hanan, Fazal (International Journal of Pathology, 2022)
Background: Four different serotypes (DEN1, DEN2, DEN3 and DEN4) are implicated in either Dengue fever (DF), Dengue Hemorrhagic Fever (DHF) or Dengue shock syndrome (DSS). DHF are often a consequence of mixed/double infections with two different genotypes or secondary viral infection. In the past few years, Pakistan has faced several sporadic outbreaks of dengue fever that eventually developed into a significant epidemic in 2011, 2017, 2018 and 2019, with dire consequences for public health. This study was carried out to investigate different dengue virus genotypes in patients with classical dengue fever and further investigate the patients for mixed infection. Methodology: A total of 200 blood samples from classical dengue fever patients were collected during September-December 2011 and 2019 were used for isolation of sera. Presence of virus was initially investigated through Immuno-Capture ELISA (IC-ELISA). ELISA positive samples were further probed through RNA-based nested RT-PCR. For DEN-genotyping total RNA was extracted from patients’ sera and was reverse transcribed into cDNA; serotypes-specific primers were used for validation of various genotypes. Results: Through RT-PCR, majority (51.85%) of the patients tested positive for serotype 2, followed by serotype 3 (42.59%) and only 5.55% of patients had mixed infection (both DEN2 and DEN3). None of the samples tested positive for DEN1 and DEN4. Conclusion: It would be interesting to emphasize on cases where patients with Classical dengue fever had double-dengue-virus-genotype-infection exhibit full recovery. We believe investigating such cases would provide clues to devising treatment for sever dengue hemorrhagic disease.